The Washing - Hawes, Alison (China Oxford University Press, 1999)
Presents a literacy programme designed to guide schools through the primary years, aimed to meet the requirements of the National Literacy Strategy, National Curriculum in England and Wales, English Language 5-14 in Scotland, and Common Curriculum in Northern Ireland. The "Fiction" strand contains stories, events, and illustrations.
Include color Illustrations
Keywords: a